Effect of traumatic exposure on thymus weight level after dexamethasone application in rats - Knežević, Milica; Ivanišević, Milica; Kojović, Natalija; Starčević, Ana (Medicinski podmladak, 2022)
ABSTRACTIntroduction: Thymus is the central lymphoid organ responsible for proper immune cell maturation, hence ensuring functional T cell repertoire. Stress induces elevated levels of hormones that profoundly alter immune response. Susceptibility to endogenous and exogenous glucocorticoids make thymus ideal substrate for anatomical and morphological analysis.Aim: Our research aimed to investigate the impact of endogenous and exogenous glucocorticoids on thymus weight level.Materials and methods: Experimental procedure was conducted on male Wistar rats divided into 2 groups- control and experimental. Latter was exposed to two kinds of stressors. Acute stress included immobilization with exposure to the predator’s odor. Chronic social stress included rotation of the animals held in pairs. On the 11th day of the experimental procedure, half of the experimental group received dexamethasone treatment (impact of endogenous+ exogenous glucocorticoids) while the other half did not (impact of endogenous glucocorticoids). After the experiment, animals were sacrificed and their thymuses were obtained and measured. For statistical analysis, ANOVA was used to test differences between groups and LSD test for each group testing.Results: Results showed statistically significant differences between the thymus mass of different groups (F=4.336, p=0.048). The part of the experimental group that received dexamethasone had a smaller thymus weight level compared to the part of the experimental group that received no treatment (p=0.024). No statistically relevant results were obtained after comparing thymus masses from stress without dexamethasone and control group (p>0.05).Conclusion: Our results support the fact that exogenous glucocorticoids induce morphological changes in thymus which are observed in decreased weight level. Stress induced thymus apoptosis was not sufficient to lead to decrease in thymic mass. Our further experiments will put emphasis on understanding of morphological and anatomical changes caused by stress.
Keywords: thymus, stress, dexamethasone, glucocorticoids